Answer:
p=-9
Step-by-step explanation:
132=-6+3 (1-5p)
-6+3 (1-5p)=132
-6+3 (1-5p)+6=132+6
3(1-5p)=138
3(1-5p)/3=138/3
1-5p=46
1-5p-1=46-1
-5p=45
p=-9
The rate of change is 8/6.
Answer:
<h2>P(x) = (x+3)(x-2)^2</h2>
Step-by-step explanation:
Looking at the brackets you can see where the curve will intersect the x-axis.
The graph shows the curve intersecting at (0,-3) and (0,2).
This means:
x = -3
AND
x = 2
Rearrange the equations, equating them to 0.
x + 3 = 0
x - 2 = 0
This will be the values in the brackets.
Because the curve only touches 0,2 and DOES NOT cross it, we know that x - 2 is a repeated root, hence (x-2) is squared.
Therefore your brackets are: (x+3)(x-2)(x-2)
Which can be simplified:
(x+3)(x-2)^2
Where ^2 means squared.
Answer:
79.95
Step-by-step explanation:
The first step is to rewrite the percentages into decimals so they can be added or subtracted easier. To turn a percentage into a decimal, remove the percent sign and move the decimal two spaces to the left (in other words, divide the number by 100).
12% becomes -0.12
8% becomes 0.08
Now, let's solve.
79.99 - 0.12 + 0.08
Evaluating 79.99 - 0.12, the equation becomes 79.87 + 0.08.
Evaluating 79.87 + 0.08, we get the final answer, 79.95.